Our Lady of Bewilderment : Poems - Pelegrin, Alison (Book collections on Project MUSE., 2022)
"Whether by way of visitations from secular saints, hauntings from childhood, or the lingering damage of physical and mental trauma, the world speaks to and through Alison Pelegrin in Our Lady of Bewilderment. Thankfully she listens, and the result is her most humorous, honest, and intimate collection of poems to date. The first section, "Rituals for Serving Ambrosia," explores shadowy undertones of memory and childhood. At the heart of the book lies a series of lamentations, gathered in 'Razor Days' and 'Rage Goddess,' while the poems of 'That Which Does Not Kill Us' serve as a sort of redemption. The sections are linked by a series of Feast Days poems. In these jubilant nonce sonnets, the speaker celebrates the imperfect beauties of a world that seems a strange familiar to her-she knows where she is but not where she stands. Our Lady of Bewilderment showcases Pelegrin's gifts as an unusual blend of mystic-comedian, exploring physical and psychic beauty and terror without losing sight of wonder"--